Feeling without localizing: exploring tactile misperception in a patient with uncommon parietal left brain damage - Have, Laurence; Quesque, François; Priot, Anne-Emmanuelle; Chastres, Véronique; Revol, Patrice; Delporte, Ludovic; Chabanat, Eric; Obadia, Nathalie; Cotton, François; Reilly, Karen T.; Rossetti, Yves (Frontiers in Human Neuroscience, 2023)
Abstract There is a long tradition in neuropsychology to link brain lesions to specific pathological presentations. We report a very unique clinical presentation of a patient who complained, after a left parietal brain damage, about feeling tactile stimulations on his right upper limb without being able to localize them. Using a single case study approach, we report three experiments relying on several custom-made tasks to explore the different levels of somatosensory information processing, ranging from somato-sensation to somato-representation. Our results showed a preserved ability to localize tactile stimuli applied on the right upper limb when using pointing responses while the ability to localize was less efficient when having to name the stimulated part (akin Numbsense). When the stimuli were applied on more distal locations (i.e. on the hand and on fingers), the number of correct responses decreased significantly independently of the modality of response. Finally, when visually presented with a stimulus delivered on the hand of an examiner in synchrony with the stimulation on the hidden hand of the patient, responses were largely influenced by the visual information available. Altogether, the convergence of these different customized tasks revealed an absence of autotopagnosia for motor responses for the right upper limb, associated with altered abilities to discriminate stimulus applied on distal and restricted/closer zones in the hand. The somato-representation of our patient seemed to significantly rely on visual information, leading to striking deficits to localize tactile stimuli when vision and somesthesic afferences are discordant. This case report offers a clinical illustration of pathological imbalance between vision and somesthesia. Implications of these troubles in somato-representation on higher cognitive level processes are discussed.